TOURISM DEVELOPMENT AND CULTURAL PRESERVATION IN TENGANAN VILLAGE, KARANGASEM, BALI - Anisa Fadila (Media Inovasi Pendidikan dan Publikasi, 2023)
Tenganan village has over a thousand years of history, making it one of the oldest villages in Bali. Before the great influence of Hindu-Buddhism on the island, the Bali Aga people lived in Tenganan, showing their strong cultural roots. Tenganan village has a unique culture, dances, and traditional games. This research aims to study how culture, tourism, and the problems faced by the people of Tenganan Village in Bali relate to each other. The focus of this research lies on how successful cultural preservation, tourism management, and its effects on the lives of local people. The main objective is to show how Tenganan Village overcomes the impact of modernization and tourism growth while maintaining their unique culture. This paper discusses how local wisdom, community participation, and management policies can play an important role in maintaining a balance between economic development and preservation of cultural identity through a multidimensional approach. It concludes that Tenganan Village in Karangasem, Bali, is a clear example of how communities can maintain their culture despite being affected by tourism and technological advances. The role of customs, community participation, and natural resource management is crucial to maintain the balance between cultural preservation and economic development.